Peran Aplikasi Notion dalam Perkuliahan untuk Mewujudkan Produktivitas Mahasiswa - ., Amelia Cahyani; ., Divani Agustin; ., Intan Muslimah; ., Nuraida Khulliyatunnisa (CV. ITTC INDONESIA, 2023)
This study aims to explore the role of the Notion application in increasing student productivity in lectures. The quantitative method was used by sending online questionnaires to 67 students from various institutions in Indonesia, including users and non-users of Notion. The data obtained were analyzed using descriptive statistical techniques to assess the significant impact of the Notion application on student productivity. The research results show that Notion helps students manage schedules, create task lists, and organize lecture notes more efficiently and effectively. This application also makes it easy to manage complex tasks. Notion's strength lies in its accessibility, which allows students to access information and documents from their mobile or desktop devices anytime and anywhere. Notion has become a popular choice for college students to increase their day-to-day productivity. With Notion, students can tackle various tasks such as writing notes and setting reminders without the need to use paper, but via a smartphone or laptop device.